Testing Machine for Investigation of Thermal State of Air Cooling Diesel Engine - A. A. Turochkin (Наука и техника)
The paper presents a testing machine for investigation of thermal state of a small-sized air cooling MD- 10-type engine. In order to assess the level of heat-release rate of the engine a cylinder is selected and the method of its temperature measurement is described. The paper reveals the method for manufacturing of thermocouples without soldering.